Quality of life after restorative proctocolectomy and ileal pouch-anal anastomosis in patients with familial adenomatous polyposis: a matter of adjustment - Wolf, Nadine D.; Kadmon, Martina; Wolf, Robert Christian; Brechtel, Anette; Keller, Monika (Colorectal disease, 2011)
Aim: Favourable outcomes for health-related quality of life (HRQL) have been reported in patients with familial adenomatous polyposis (FAP) after restorative proctocolectomy and ileal pouch-anal anastomosis (RPC). However, less is known about patients’ subjective experience and adjustment to postoperative impairment. Using a multidimensional psychometric assessment, we investigated patient-reported HRQL to determine the impact of the patient’s subjective experience together with medical, functional and psychosocial factors on HRQL. Method In this cross-sectional study, 116 FAP patients who had undergone RPC on average 8 years earlier completed standardized and study-specific questionnaires and participated in a personal interview. The impact of medical, functional and psychosocial factors on patients’ HRQL was determined by regression analyses. Results When using a generic psychometric measure, FAP patients’ overall HRQL was comparable with that of the general population. Impaired HRQL, however, was found in patients reporting poor pouch function in contrast to those reporting good or moderate functional outcome. Findings from a personalized interview also suggested that a good functional result does not necessarily translate into good HRQL. Personal resources predicted patients’ physical and psychological well-being, whereas little variance of HRQL was explained by medical factors and function. Conclusion Patients’ HRQL is, to a substantial degree, the result of adjustment to the adverse impact of RPC. By using personal resources the majority of patients may achieve satisfactory HRQL levels even when bowel function is impaired. A multidimensional assessment that comprises medical, functional and psychosocial aspects is required to ascertain an adequate evaluation of FAP patients after RPC.
Gesehen am 24.11.2022